Africa Emerges consummate challenges, abundant opportunities - Rotberg, Robert I. (Cambridge Polity Press, 2013)
Sub-Saharan Africa is no longer a troubled ?dark continent.? Most of its constituent countries are now enjoying significant economic growth and political progress. The new Africa has begun to banish the miseries of the past, and appears ready to play an important role in world affairs. Thanks to shifts in leadership and governance, an African renaissance could be at hand.
Includes bibliographical references
Keywords: Africa